Pengaruh Sistem E-Filling Dan E-Billing Terhadap Kepatuhan Wajib Pajak dengan Pemahaman Internet Sebagai Variabel Moderating Pada Wajib Pajak Orang Pribadi yang Terdaftar - Sinaga, Claudia Chery Yoranda; Satya Azhar, Mhd. Karya (Graha Mitra Edukasi, 2023)
The tax collection system is a tax collection process in which taxpayers are required to pay taxes owed to the government. There are 3 recognized tax collection systems in Indonesia, namely the Withholding System, Self Assessment System, and the Official Assessment System. Indonesia has replaced the tax collection system from the Official Assessment system to the Self Assessment system. In the Self Assessment System system, taxpayers are entrusted with calculating, paying, and self-reporting the amount of tax that should be owed based on tax laws and regulations. This study aims to determine the factors that affect taxpayer compliance. The sample used in this study were all individual taxpayers who were registered as mandatory SPT at KPP Pratama Medan Timur as many as 100 respondents with the slovin method.The results of this study indicate that the E-Filling System has an effect on Taxpayer Compliance, the E-Billing System has an effect on Taxpayer Compliance, Understanding the Internet can moderate the effect of the E-Filling System on Taxpayer Compliance, Internet Understanding can moderate the effect of the E-Billing System on Compliance Taxpayer.